This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
find the difference from the previous number ,multiply it by 3 and add into the number will get a next number
4-2 =2, 2 *3 =6 , 6 +4 = 10
10-4 =6, 6 * 3 =18 , 18 + 10 =28
28-10 =18, 18 * 3 = 54 , 54 + 28 = 82
By keen observation, you can notice that the x t h number in the pattern is: 3 x − 1 + 1 . Therefore the fourth number in the pattern is 3 4 − 1 + 1 = 2 7 + 1 = 2 8
Problem Loading...
Note Loading...
Set Loading...
It's easy to tackle a problem by factoring out a common number to find a pattern. 2 ( 1 , 2 , 5 , x , 4 1 , 1 2 2 , 3 6 5 ) Its easy to realise that the n t h term is the sum of the previous term and 3 n − 2 . So, the original series would differ by 2 × 3 n − 2
In this case, the 4th term would be 1 0 + 2 × 3 2 = 2 8